A Black women's history of the United States - Berry, Daina Ramey; Gross, Kali N., 1972- (Revisioning American history., 2021)
"A vibrant and empowering history that emphasizes the perspectives and stories of African American women to show how they are--and have always been--instrumental in shaping our country. In centering Black women's stories, two award-winning historians seek both to empower African American women and to show their allies that Black women's unique ability to make their own communities while combatting centuries of oppression is an essential component in our continued resistance to systemic racism and sexism. Daina Ramey Berry and Kali Nicole Gross offer an examination and celebration of Black womanhood, beginning with the first African women who arrived in what became the United States to African American women of today. A Black Women's History of the United States reaches far beyond a single narrative to showcase Black women's lives in all their fraught complexities. Berry and Gross prioritize many voices: enslaved women, freedwomen, religious leaders, artists, queer women, activists, and women who lived outside the law. The result is a starting point for exploring Black women's history and a testament to the beauty, richness, rhythm, tragedy, heartbreak, rage, and enduring love that abounds in the spirit of Black women in communities throughout the nation."--Publisher's website.